2012
DOI: 10.1007/s00701-012-1529-4
|View full text |Cite
|
Sign up to set email alerts
|

Large and giant vestibular schwannomas: does cisterna magna hyperproteinorrhachia influence visual status?

Abstract: Elevated cisternal CSF proteins may play an important role in determining visual outcome in large to giant VSs. Ventricular CSF analysis is often unable confirm the presence of VS-associated cisternal hyperproteinorrhachia. High CMCP levels may influence decision-making while instituting a permanent CSF diversion for postoperative hydrocephalus or recalcitrant pseudomeningocoele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They also can produce problems with CSF absorption from protein leaking into the CSF. 6,7 In the present case, disc oedema was present in the absence of obstructive hydrocephalus. A strong possibility is the role of hyperproteinorrhachia in causing CSF stasis.…”
Section: Discussionmentioning
confidence: 72%
“…They also can produce problems with CSF absorption from protein leaking into the CSF. 6,7 In the present case, disc oedema was present in the absence of obstructive hydrocephalus. A strong possibility is the role of hyperproteinorrhachia in causing CSF stasis.…”
Section: Discussionmentioning
confidence: 72%
“…Among the western series, the incidence ranges from 1 to 10%, while in developing world series, it varies from 6.2 to 57.5% ( Table 5 ). 3 4 5 6 7 8 9 10 Actual incidences may differ due to underreporting. In the Western world, patients seek medical attention early at the onset of symptoms; therefore, small tumors are detected early.…”
Section: Discussionmentioning
confidence: 99%
“…In logistic regression analysis, duration of symptoms, papilloedema, hydrocephalus, and tumor volume was not significant for visual loss. 5 Shedding of protein through the tumor capsule was the probable cause. Protein concentration in ventricular CSF was also higher in their study.…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of hydrocephalus was comparable between the two groups, it is likely that raised intracranial pressure was greater in the group with tumors ≥5 cm in size, as evidenced by the increased incidence of papilledema at earlier presentation. Kumar et al, [14] have shown that independent of the tumor volume, elevated cisternal CSF proteins may play an important role in determining the presence of papilledema and visual outcome in giant VSs. The presence of an increased incidence of diplopia due to a unilateral sixth nerve paresis in this group with tumors ≥5 cm in size also may be attributed to the size of the tumor and direct compression of the abducens nerve rather than a generalized raised intracranial pressure, which causes a bilateral lateral rectus paresis.…”
Section: Clinical Presentationmentioning
confidence: 99%